Business Process Digitization in “Marbil Collection” Home Industry Using Business Process Model and Notation - Nadya Kumalasari; I Kadek Dwi Nuryana (Universitas Negeri Surabaya, 2025)
Digital transformation has become an essential requirement for small and medium enterprises, including home industries engaged in handicrafts such as bag production. However, most home industry players still run business processes manually, potentially causing various operational problems such as production delays, distribution inaccuracies, and order recording errors. This research aims to analyze and re-model business processes at Marbil Collection, a home-based business that produces bags on a make-to-order basis. The approach used was Business Process Model and Notation (BPMN), a visual standard for systematically describing business workflows. This research identified four main processes in operations, namely ordering, procurement of raw materials and production, distribution and order completion, and employee payroll. These processes were mapped in the current business process model (as-is), and then redesigned into a proposed model (to-be) that supports automation and digitization. The results of the modeling showed significant gaps in the manual system used, especially in terms of service speed, transparency, and documentation. The proposed digital process design provides a structured solution to improve efficiency, accuracy, and customer experience. This research is expected to be the basis for developing a simple information system that suits the needs of the home industry, as well as making a practical contribution to similar businesses that want to start digitalization from an understanding of their own business processes.